The Relationship between Self-Efficacy and Self-Care in Heart Failure Patients at Home Sick Dr. Bratanata, Jambi City - Utami, Fitri; Oktarina, Yosi; Nurlinawati, Nurlinawati (Jurnal Keperawatan Universitas Jambi, 2024)
Heart failure was one of the number one causes of death in Indonesia in 2018 at 1.5%. Heart failure can result in the patient's inability to carry out self-care. Self-care can be influenced by self-efficacy where self-efficacy can encourage the process of self-control in carrying out self-care. This research is a quantitative descriptive research with a correlative descriptive research design with a cross sectional approach. The total sample was 74 respondents with heart failure, sampling used purposive sampling technique. The instrument used is the SCHFI questionnaire for self-care and CSE Scale questionnaire for self-efficacy. Univariate data analysis used frequency distribution and bivariate analysis used the Chi Square statistical test. There were 45 heart failure respondents with high self-efficacy (60.8%), 29 people with low self-efficacy (39.2%). 38 people (51.4%) had high self-care and 36 people (48.6%) had low self-care. From the results of the Chi Square analysis, the p-value was 0.000 (<0.05). There is a relationship between self-efficacy and self-care in heart failure patients at Dr. Hospital. Bratanata Jambi. It is hoped that nurses can provide health promotion in the form of motivation to increase self-efficacy in heart failure patients in carrying out self-care.